B2(OH)4 and Et3N-BH3: A New Combination of Reagents for the Mild and Efficient Photoreduction of Nitro(hetero)arenes - Błyszczyk, Piotr T.; Roure, Baptiste (Synthesis, 2024)
Anilines are a common motif in many bioactive compounds and their production through the reduction of nitroarenes has become an essential method for their synthesis. We demonstrate that the combination of an amine-borane complex and hypoboric acid (tetrahydroxydiborane) under visible light irradiation can accomplish the reduction of nitroarenes to the corresponding anilines. Preliminary mechanistic studies suggest the generation of boryl radicals via a hydrogen atom transfer (HAT) step from the photoexcited nitroarene. Involvement of a parallel thermal pathway is demonstrated with the high reaction efficiency being partially attributed to both routes.
Keywords: boron; radical; nitroarene; aniline; reduction; photochemistry; mechanism